Analysis of the Fractional-Order Kaup–Kupershmidt Equation via Novel Transforms - Naveed Iqbal; Humaira Yasmin; Ali Rezaiguia; Jeevan Kafle; A. Othman Almatroud; Taher S. Hassan (Journal of Mathematics)
In this article, we develop a technique to determine the analytical result of some Kaup–Kupershmidt equations with the aid of a modified technique called the new iteration transform method. This technique is a mixture of the novel integral transformation Elzaki transformation and the new iteration technique. The nonlinear term can be handled easily by a new iteration technique. The results show that the combination of the Elzaki transformation and the new iteration technique is quite capable and basically well suited for applying in such problems and that it can be implemented to other nonlinear models. This technique is viewed as an effective alternative approach to certain existing approaches for such accurate models.